THERAPEUTIC COMMUNICATION RELATIONSHIP WITH THE ANXIETY LEVEL OF PRIMIGRAVIDA MOTHERS IN DEALING WITH LABOR IN HJ. SHOLIHA BIDAN BANTAR GEBANG - Maretyas, Dhea Putri; Simamora, Rotua Suriany; Meliyana, Ernauli; Pelawi, Arabta M. Peraten; Nurhidayah, Nurhidayah (NHM PRESS, 2023)
Introduction: The purpose of this study was to determine the relationship between therapeutic communication and the level of the midwife Hj. Sholiha Bantar Gebang. The population is the first pregnant women and mothers who perform prenatal care. Samples were obtained by purposive sampling. The research was conducted in July. Analysis of the data used is SPSS. Based on the calculation, the calculated value is -0,000 with a significant value of 0,05 (p<0,05). The conclusion is that there is a relationship between therapeutic communication and the level of anxiety of the first pregnant women facing childbirth at the midwife Hj. Sholiha Bantar Gebang.